Revisiting the determinants of house prices in China's megacities: Cross-sectional heterogeneity, interdependencies and spillovers - Chunping Liu; Zhirong Ou (Cardiff University, Cardiff Business School, 2021)
We revisit the determinants of house prices in Chinaís megacities. Previous work on similar topics fails to account for the widespread cross-sectional heterogeneity and interdependencies, despite the importance of them. Using a PVAR estimated by the Bayesian method allowing for these features, we Önd each city is rather unique, especially on the extent to which local house prices are disturbed by external house price shocks. The spillovers are mainly due to direct housing market interdependence, which seems related more to demand before 2010, but more to supply thereafter due to property purchase restrictions. The new evidence we establish therefore suggests that city-level stabilisation of house prices should fully respect local features, including how local markets respond to external disturbances.
Keywords: C11; R15; R31; 330; houseprice; Chinese megacities; PVAR; cross-sectional heterogeneity and interdependencies